Effects of the Silicate Modulus of Water Glass on the Hydration and Mechanical Properties of Alkali-Activated Blast Furnace Ferronickel Slag - Liu, Kuisheng; Liu, Zhenguo; Sun, Jianwei (Frontiers in Materials, 2021)
Blast furnace ferronickel slag (BFNS), currently an underutilized metallurgical residue, was investigated for use as a precursor for alkaline activation. Water glass solutions with various moduli (0.5, 1.0, 1.5 and 2.0) were used at the same water glass concentration of 10% to investigate the influence of the modulus on hydration and mechanical properties. The results show that the modulus has a certain impact on the hydration and mechanical strength development of alkali-activated BFNS. Increasing the modulus of water glass does not change the type of hydration product and the activity of the Mg-containing phases, but it decreases the amount of C2AS, the Ca/Si and Al/Si ratios of the (N,C)-A(M)-S-H gel. In addition, a high silicate modulus deteriorates the pore structure, which has an adverse effect on the development of compressive strength and splitting tensile strength.